Clinical comparison of two human papillomavirus detection assays: GenoFlow and reverse line blot - Fatimah S Alhamlan; Hadeel H Khayat; Dalia A Obeid; Asma M Tulba; Teejan S Baduwais; Mohamed B Alfageeh; Mohammed N Al-Ahdal (Journal of Infection in Developing Countries)
Introduction: Human papillomavirus (HPV) infection is typically critical in the oncogenesis of cervical cancer. However, available HPV detection kits differ in their ability and sensitivity to detect various types of HPV, and this variability has led to inconsistencies in the reporting of the geographic prevalence of HPV types, especially in developing countries. Here, we compared results of the recently developed GenoFlow HPV array test, which detects 33 HPV genotypes, to those of the well-established reverse line blot (RLB) assay, which detects 23 HPV types.